The collection of the genus Mispila Pascoe, 1864 housed in the Natural History Museum, London (Coleoptera: Cerambycidae) - Xie, Guanglin; Barclay, Maxwell V. L.; Wang, Wenkai (Zootaxa, 2023)
Data on the collection of the genus Mispila Pascoe, 1864 (Lamiinae, Pteropliini) deposited in the Natural History Museum, London are presented. Mispila (s. str.) auguralis Pascoe, 1878 is removed from synonymy with Mispila (s. str.) venosa Pascoe, 1864 and considered as a subspecies: Mispila (s. str.) venosa auguralis Pascoe, 1878 stat. rev.. Lectotypes are designated for Mispila (s. str.) obscura Gahan, 1890 and Mispila (Dryusa) flexuosa (Pascoe, 1864). The variation of Mispila venosa venosa Pascoe, 1864 is shown. A total of 20 valid species/subspecies are listed.